Diabetes Mellitus among Male Students of Jeddah University in Saudi Arabia - Alhasan, Ahmed Hassan; Aljunaid, Mohammed A.; Abid, Ahmed Z.; Hakeem, Moayad; Alzain, Meshari; Hassanien, Gamal H; Al-Nazzawi, Mohammed T.; Jelaidan, Jawaher H.; Basaeed, Lamis F. (Arab Journal for Sciences and Research Publishing, 2016)
Aim: To screen for diabetes among students of Jeddah University in the KSA. Methodology: A cross sectional descriptive study involved n= 42 students of Jeddah University in the KSA who are 18 to 21 years of age. Random sampling methods used, data were collected by measuring random blood glucose level (RBG) of all participants by using glucometer (Bioniam GM300), for four months from 2 April 2014 to 12 of August 2014. Results: 4.76% students had a high level of blood sugar, which classified as prediabetes, the most of students showed an ideal level of random blood glucose to be 95.25% in which RBS level below 140 mg/dL. Conclusion: Male students of Jeddah are free from diabetes mellitus.